Comparison of the anaesthetic effects of 4% articaine hydrochloride and 2% lidocaine hydrochloride for maxillary molar extraction: A randomized double blind crossover study - Olufemi Adigun; Chibuzo Chimezie Uguru; Oladimeji Adeniyi Akadiri (Elsevier, 2022)
Many reports in Europe and America have suggested that articaine has superior dental.anaesthetic properties over lidocaine. However, none of these studies was carried out in a black population. This study was designed to evaluate if the reported superior efficacy of articaine compared to lidocaine as a local anaesthetic agent for dental extraction is equally applicable to infiltration anaesthesia in a black population. Patients between ages of 18-40 years were selected for the study. The result showed that articaine had a faster onset of anaesthesia and longer duration of action compared with lidocaine, however the differences were not statistically significant. The median times of onset were 2.60 min and 2.88 min for articaine and lidocaine respectively; while the median durations of anaesthesia were 31.45 min and 30.46 min for articaine and lidocaine respectively. Articaine also achieved more profound anaesthesia compared with lidocaine; 87.5% compared to 62.5% of participants indicated zero point on a 10 cm visual analog scale (VAS), and 12.5% compared to 37.5% marked the 1 cm point on the scale in Articaine and Lidocaine groups respectively. Articaine diffused through the maxilla from buccal infiltration to cause palatal anaesthesia better than lidocaine; as 75% compared to 50% indicated the 1 cm point and 0% compared to 25% indicated the 2 cm point on VAS in Articaine and Lidocaine groups respectively. Therefore, the choice between 4% Articaine and 2% Lidocaine in dental practice should be based on personal preference since the two agents are both safe and have comparable properties. Clinical trial registration number: PACTR201802003023333.